2007
DOI: 10.3354/ame046055
|View full text |Cite
|
Sign up to set email alerts
|

Natural bacterioplankton assemblage composition during blooms of Alexandrium spp. (Dinophyceae) in NW Mediterranean coastal waters

Abstract: We characterised the spatial and temporal variation in the bacterioplankton assemblage composition during bloom events of different Alexandrium species (Dinophyceae) in the littoral of the NW Mediterranean Sea by means of catalysed reporter deposition fluorescence in situ hybridisation with oligonucleotide probes (CARD-FISH). We studied several Alexandrium blooms through their seasonal development (at La Fosca beach) or in their spatial variability (in Arenys Harbour and Olbia Bay), and we complemented these o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
23
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 73 publications
8
23
1
Order By: Relevance
“…The overall community composition of the Gymnodinium catenatum cultures was similar to that reported by previous studies of dinoflagellates (Alavi et al 2001, Hold et al 2001b, Jasti et al 2005, Pérez-Guzmán et al 2008. In particular, the broad distribution of phyla is similar to that reported from field samples, where Alphaproteobacteria and, especially, the Roseobacter and Bacteroidetes (Flavobacteria primarily) were the principal taxa associated with dinoflagellate blooms (Fandino et al 2001, Wichels et al 2004, Garcés et al 2007). However, as noted by earlier studies, the overlap between culture studies and field bloom-associated bacteria at the individual phylotype level is often very low (Garcés et al 2007).…”
Section: Bacterial Diversity Associated With Gymnodinium Catenatumsupporting
confidence: 85%
“…The overall community composition of the Gymnodinium catenatum cultures was similar to that reported by previous studies of dinoflagellates (Alavi et al 2001, Hold et al 2001b, Jasti et al 2005, Pérez-Guzmán et al 2008. In particular, the broad distribution of phyla is similar to that reported from field samples, where Alphaproteobacteria and, especially, the Roseobacter and Bacteroidetes (Flavobacteria primarily) were the principal taxa associated with dinoflagellate blooms (Fandino et al 2001, Wichels et al 2004, Garcés et al 2007). However, as noted by earlier studies, the overlap between culture studies and field bloom-associated bacteria at the individual phylotype level is often very low (Garcés et al 2007).…”
Section: Bacterial Diversity Associated With Gymnodinium Catenatumsupporting
confidence: 85%
“…Even though associations of Alphaproteobacteria and Gammaproteobacteria with microalgae have been reported in different studies (Hold et al 2001, Grossart et al 2005, Garcés et al 2007), we measured only weak relationships, as indicated by low R values (Table 4) with low slopes across the gradient of chl a at the global scale for SAR11 and Gamma pro teobacteria with slopes of 0.13 ± 0.04 and 0.22 ± 0.05, respectively. However, these relationships changed when the type of ecosystem was taken into account.…”
Section: Bcs−chl a Relationships In Coastal And Open-ocean Conditionsmentioning
confidence: 55%
“…5). Although in marine systems, the dynamics of CF were linked to the blooms of distinct diatoms (Pinhassi et al 2004, Grossart et al 2005 or dinoflagellates (Garcés et al 2007), only low proportions of CF were scored positive for leucine and also for glucose incorporation over the whole season in the lacustrine part of the reservoir, where marked changes in EPP (Fig. 2) and phytoplankton composition (2imek et al 2008) were observed.…”
Section: Group-specific Activities Based On Mar-fishmentioning
confidence: 97%